A Study of Factors Contributing to Denture Stomatitis in a North Indian Community - Amit Vinayak Naik; Ranjana C. Pai (International Journal of Dentistry)
Factors like oral and denture hygiene, presence of saliva, age of the denture, and degree of colonization with Candida albicans are to be evaluated as local contributing factors for causing denture stomatitis. 100 patients aged 30 to 70 years were selected for the study. Among these, 70 patients were labeled test group showing signs of stomatitis and 30 patients as control group as they showed no inflammatory signs. Clinical tests included oral and denture hygiene evaluation, salivary measurements, and age of the dentures, and microscopic investigations were done. Results showed no significant differences between the two groups in terms of saliva, oral and denture hygiene habits, and denture age. Test group showed stomatitis in patients who were wearing dentures for 5 to 10 years compared to control group who were wearing dentures for 10 years and above. Denture age was proportional to Candida colonization and not to degree of inflammation. Significant differences were found in Candida colonization of the fitting surface of the denture between stomatitis and control groups. Poor denture hygiene habits are the most prominent contributing factor for denture stomatitis and colonization.